Political Communications Transformed - Bartle, John. author. aut Link
XIII, 210 p.
Keywords: Dramatic changes in society, technology and culture have transformed the relationship between political parties, the media, and the individual voter over the last fifty years. The leading researchers gathered in this volume offer a comprehensive analysis of the evolution of British political communication since 1945. They explore the competition for coverage between political parties and media organizations, the ongoing rivalry between politicians and the press, and the implications for the quality of British democracy.